3ab+6=

Simple and best practice solution for 3ab+6= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3ab+6= equation:


Simplifying
3ab + 6 = 0

Reorder the terms:
6 + 3ab = 0

Solving
6 + 3ab = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + 3ab = 0 + -6

Combine like terms: 6 + -6 = 0
0 + 3ab = 0 + -6
3ab = 0 + -6

Combine like terms: 0 + -6 = -6
3ab = -6

Divide each side by '3b'.
a = -2b-1

Simplifying
a = -2b-1

See similar equations:

| -15+2n=73 | | 3(x+5)-6=x-7 | | -3n^2(-2n^5+5n-5)= | | 7x=-13 | | 12x+1y=94 | | -200+25(4)= | | 6(2z+3)=-54 | | -200+25(2)= | | -(9x-8)=-5(3x-10) | | 3b-(b+2)=5-(3-b) | | (4y+3)=(y-2) | | 21x-5=7+15y | | 7(6x+10)=280 | | 9a^2(-5a^3+5a-5)= | | 4-8a=4(1-2a) | | 4sin^2(x)=2 | | 3g+5=7b-7.4 | | .35x+.30x=22.75 | | 8(n+6)+8=7n | | .35x+.30x=2275 | | -20=5x+5x+10 | | 9z=40500 | | -x-4=7x-68 | | (3p-7)=(5p-6) | | 10-6x+3x=-2 | | 29=76-46 | | 2(n+2)=5-5n | | 720=12x+100 | | -3n^5(5n+4)= | | 5m+6+4(3m-5)-5(m+5)=0 | | 7x+-4=1x+32 | | 12n+2(n-3)=1+5(2n-1) |

Equations solver categories